Flexible Working Arrangements and Work-Family Culture Effects on Job Satisfaction: The Mediation Role of Work-Family Conflicts among Female Employees - Aura, Nadya Alsyifa Mawira; Desiana, Putri Mega (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2023)
Objective: This study examines the relationship between flexible working arrangements and work-family culture by the mediating role of work-family conflict on the job satisfaction of female employees. Methods: This study was conducted on 295 female workers in Information and Communication Technology (ICT) service companies. The data were collected from an online survey using a 6-Point Likert scale following a non-probability sampling method with a purposive sampling technique which was a sampling method based on specific predetermined standards. The data was analyzed using Lisrel 8.80 through Structural Equation Modelling (SEM). Findings: The results indicate that flexible working arrangements positively and significantly impact work-family conflict and job satisfaction. Additionally, Work-Family Culture has a negative and significant impact on Work-Family Conflict but a positive and significant impact on Job Satisfaction. Meanwhile, Work-family conflict significantly and negatively affects job satisfaction. Another finding is that the relationship between flexible working arrangements and job satisfaction and the impact of work-family culture can be partially mediated by work-family conflict. Originality/Value: Research on work-family variables tends to be mostly studied in the United States and Anglo Countries (U.K., Australia). However, research on this subject in Asia is limited, despite the fact that female employees in this region experience work-family conflicts more frequently. To fill this gap, this study was conducted in Indonesia, Southeast Asia. The findings of this research may also be relevant to other Asian countries that share similar characteristics. Practical/Policy implication: The company's human resources management should implement a family-friendly work culture (WFC) by encouraging and respecting employees' integration of work and family life to prevent and minimize conflict between work and family roles or called Work-Family Conflict (WFCON) during Flexible Working Arrangements (FWA).